2012
DOI: 10.1128/jb.00158-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Pattern-Forming Social Bacterium Paenibacillus dendritiformis C454 Chiral Morphotype

Abstract: i Paenibacillus dendritiformis is a Gram-positive, soil-dwelling, spore-forming social microorganism. An intriguing collective faculty of this strain is manifested by its ability to switch between different morphotypes, such as the branching (T) and the chiral (C) morphotypes. Here we report the 6.3-Mb draft genome sequence of the P. dendritiformis C454 chiral morphotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
(9 reference statements)
1
13
0
Order By: Relevance
“…Paenibacillus dendritiformis (morphotype C; also known as the chiral morphotype) is a spore-forming, motile bacterial species (56). Each bacterium is an elongated (filamentous), rigid (seldom bends by collisions), rod-shaped cell, with a fixed thickness of ϳ1 m and a very broad length distribution of ϳ17 Ϯ 12 m. The bacteria were maintained at Ϫ80°C in Luria broth (LB) (Sigma, St. Louis, MO) with 25% (wt/vol) glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Paenibacillus dendritiformis (morphotype C; also known as the chiral morphotype) is a spore-forming, motile bacterial species (56). Each bacterium is an elongated (filamentous), rigid (seldom bends by collisions), rod-shaped cell, with a fixed thickness of ϳ1 m and a very broad length distribution of ϳ17 Ϯ 12 m. The bacteria were maintained at Ϫ80°C in Luria broth (LB) (Sigma, St. Louis, MO) with 25% (wt/vol) glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Paenibacillus dendritiformis is an interesting bacterial species marked by the complex spatial organization of its colony, which can form different patterns of growth on semi-solid agar such as chiral branches, swirls, and vortices [67,68]. It was observed that the sibling P. dendritiformis bacterial colonies grown on low-nutrient agar medium mutually inhibited the growth of each other [69].…”
Section: "Forced Suicide" In Paenibacillus Dendritiformismentioning
confidence: 99%
“…Moderately thermophilic E. profundum was defined by Crapart 15 but its industrial enzyme abilities never examined while lipase production of E. profundum discovered in this study. P. dendritiformis, which was included in the genus Bacillus, was first discovered in 1990s and reclassified as a separate genus 49 . However, there is no record about P. dendritiformis from thermophilic sources while protease production was determined in this study.…”
Section: Enzyme Production Capacities Of Thermophilesmentioning
confidence: 99%